Solusi Efisiensi Pertanian: Rancang Bangun Perangkat Otonom, Detektor Mutu, dan Pisau Ganda Berbasis IoT Bagi Traktor Roda Dua Konvensional - Gabriella Sunsugos Sianturi; Lie Jasa (Majalah Ilmiah Teknologi Elektro, 2025)
The issue of limited human resources in the agricultural sector, particularly in terms of labor availability, has led to increased operational costs and decreased harvesting efficiency. On the other hand, existing IoT-based tractors are generally large-scale and expensive, making them inaccessible to smallholder farmers. To address this challenge, this study proposes the development of a modular attachment for conventional two-wheeled tractors. The device is designed to be efficient, affordable, and capable of minimizing dependence on human labor without requiring the replacement of the main tractor unit. The proposed solution includes a dual blade system (for both tilling and harvesting), a harvest quality detection system, and IoT-based autonomous navigation. All components are integrated into a single functional module that can be attached to existing two-wheeled tractors owned by farmers. This approach eliminates the need to purchase a new tractor, as the innovation enhances the functionality of equipment already in use. Additional advantages include the installation of a mechanical counterweight to stabilize the tractor during operation and the integration of quality detection capabilities, which improve efficiency by enabling simultaneous harvesting and quality monitoring. This study demonstrates that transforming conventional tractors into semi-autonomous systems can significantly enhance labor efficiency, harvesting precision, and reduce operational costs. The innovation offers a sustainable approach to agricultural modernization through the integration of modular technology and IoT, tailored for small to medium-scale farming.